Answer:
![x = (-3)/(2)](https://img.qammunity.org/2021/formulas/computers-and-technology/high-school/bf9hneaficnxdl5gxzz0c5kuwoxo031l07.png)
Step-by-step explanation:
Given
2x + y = -3
y = 4x + 6
Required
Find the value of x
2x + y = -3 --- Equation 1
y = 4x + 6 --- Equation 2
Substitute 4x + 6 for y in equation 1.
So, equation 1 becomes
![2x + 4x + 6 = -3](https://img.qammunity.org/2021/formulas/computers-and-technology/high-school/jijqna5xzft6stxv19ubtuddsv3foiilkq.png)
![6x + 6 = -3](https://img.qammunity.org/2021/formulas/computers-and-technology/high-school/muwbsxm90q9gd5yv4wrhahgcuup1rar9xc.png)
Subtract 6 from both sides
![6x + 6 - 6 = -3 - 6](https://img.qammunity.org/2021/formulas/computers-and-technology/high-school/m0mugug5g9mj2dk1ox6deeobi6lqovvgbb.png)
![6x = -9](https://img.qammunity.org/2021/formulas/computers-and-technology/high-school/zj3x84twuqqn9gqwrtqmkwww9635fya5l7.png)
Divide both sides by 6
![(6x)/(6) = (-9)/(6)](https://img.qammunity.org/2021/formulas/computers-and-technology/high-school/mdaj55y4kdlkyh5w0qlt67qps050ttb910.png)
![x = (-9)/(6)](https://img.qammunity.org/2021/formulas/computers-and-technology/high-school/jehllx9sn8cbj3entatww0v7za1yekpwsp.png)
Simplify fraction
![x = (-3)/(2)](https://img.qammunity.org/2021/formulas/computers-and-technology/high-school/bf9hneaficnxdl5gxzz0c5kuwoxo031l07.png)
Hence, the value of x is
![x = (-3)/(2)](https://img.qammunity.org/2021/formulas/computers-and-technology/high-school/bf9hneaficnxdl5gxzz0c5kuwoxo031l07.png)